Length–weight relationships of five fish species of headwater streams from upper Paraná River Basin, Southeastern Brazil - Manoel, Pedro S. [UNESP]; Brambilla, Eduardo M. [UNESP] (Hindawi, 2018)
The length-weight relationships (LWRs) of five fish species are reported. The fishes were sampled between September and December 2016 with seine net (4 mm mesh size) in 15 headwater streams from the upper Paraná River basin, Southeastern Brazil.